Will land transfer improve grain farmers’ adoption of agricultural green production technology? Evidence from Jiangxi Province, China - Yuanyuan Peng; Jinyong Guo; Yanduo Liu; Lichen Liao; Siwei Jiang; Yonghong Tang (Humanities & Social Sciences Communications)
Abstract The application of agricultural green production technologies (AGPTs) promotes green agricultural development and enhances the rural environment. Scale operations can allocate land resources rationally and modernise agricultural technology and management practices. Although previous studies have shown that expanding land transfer facilitates the adoption of AGPTs by farmers, research on how to further promote farmers’ adoption behaviour is still lacking. To understand the mechanism of land transfer on farmers’ adoption behaviour of AGPTs, this study uses survey data from farmers in Jiangxi Province, China, and employs an endogenous switching regression (ESR) model for counterfactual estimation. The results show that farmers who have acquired land through transfer adopt AGPTs at a significantly higher rate than those who have not. Land transfer promotes farmers’ adoption behaviour by increasing household income, financial support, and agricultural socialised services. Land transfer contracts, long-term transfers, and moderate land rent are also conducive to farmers’ adoption behaviour of AGPTs. The impact of the land transfer on farmers’ adoption behaviour of AGPTs is more significant among large-scale farmers, those with higher field fertility, and those with lower land fragmentation.